Analysis and Countermeasures of related factors of mental health and physical exercise of College Students - Huang, Yueqin; Guo, Chunfeng; Ouyang, Ruyang; Wang, Huaijing; Liu, Daofu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This paper examines the relationship between college students' mental health and physical exercise, analyzes the beneficial effect of physical exercise on mental health, enhances school physical education and health education, and provides a theoretical foundation for further enhancing college students' mental health. The SCL-90 was used to evaluate "the last week's" mental health condition. There are 90 possibilities on the scale, comprising 10 factors (depression, hostility, psychosis, somatization, anxiety, obsessive-compulsive symptoms, paranoia, terror, interpersonal sensitivity and others). 93% of students in certain colleges have a positive psychological experience of participating in physical activity. According to the t-test, the mental health level of college students who regularly participate in physical activity is much better than that of college students who occasionally and never participate in physical activity (P <0.01). The impact of physical activity on the mental health of college students of different genders varies. Exercise significantly improves college students' mental health; factors such as duration of physical activity, frequency of exercise, and variety of sports significantly impact mental health development.